DIAGNOSTICS OF LEARNING DIFFICULTIES OF GRADE 4 STUDENTS AT STATE PRIMARY SCHOOL 61 BANDA ACEH - Nola Fajria; Siti Mayang Sari; Fitriani Manurung; Sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Diagnostics of learning difficulties is one way that can be used to study andunderstand the problems experienced by students in teaching and learningactivities. This research aims to determine students' learning difficulties inschool subjects and the factors causing them. This research is included in thedescriptive research type using a quantitative approach. The population of thisstudy were students at State Elementary School 61 Banda Aceh consisting of164 people. Meanwhile, the research sample was 29 class IV students. The datacollection technique used was a questionnaire and analyzed using descriptivepercentage techniques. The research results show that; (1) The “Very Difficult”subject is Mathematics with a percentage of 44.82% (2) Lessons in the